Digital Marketing Strategy to Increase Product Sales at PT Mega Finance: Strategi Pemasaran Digital Untuk Meningkatkan Penjualan Produk di PT Mega Finance - Fira Firnanda; Lilik Indayani (Procedia of Social Sciences and Humanities, 2026)
General Background Technological advancements significantly shift consumer behaviors within the financial and consumer credit sectors. Specific Background Consumer finance entities, including PT Mega Finance, navigate intense market competition against digital financing providers by adapting online promotional approaches. Knowledge Gap However, prior studies often examine social media engagement and customer relationship management in isolation rather than exploring their integrated operational synergy. Aims This study investigates integrated digital marketing tactics, specifically social media engagement and direct messaging, to improve product sales and customer retention. Results Findings show that targeted Facebook and TikTok content expands audience reach, while automated direct message blasting successfully re-engages existing clients, driving higher conversion rates. Novelty This work establishes an empirical framework combining social media acquisition with database-driven re-engagement tailored for traditional non-bank financial institutions. Implications The proposed model provides a cost-effective operational roadmap for financing firms seeking sustainable competitive advantages in digital ecosystems.  Key Findings Highlights Differentiated social media channels capture distinct demographic segments effectively. Direct messaging campaigns drive higher conversion rates among existing client databases. Combining social media with database re-engagement lowers customer acquisition costs. Keywords: Digital Marketing, Sales Strategy, Customer Relationship Management, Social Media, Customer Reengagement